Algorithm for Diagnosis of Patients with Ischemic Heart Disease Depending on the Presence of Significant Coronary Artery Lesions - Yevhen Yu. Marushko; Nadiya M. Rudenko; Yana Yu. Dzhun (Ukrainian Journal of Cardiovascular Surgery, 2023)
The aim. To analyze the structure of ischemic heart disease and the prevalence of myocardial ischemia with no ob-structive coronary arteries among patients who underwent elective coronary angiography.Materials and methods. We examined 1,200 patients with a clinical diagnosis of ischemic heart disease. After coro-nary angiography all the patients with non-stenotic coronary arteries underwent hyperventilation challenge test to ex-clude vasospastic angina and echocardiographic study with intravenous administration of dipyridamole to assess the index of coronary reserve and longitudinal strain.Results. The mean age of the study participants was 59.1 ± 4.2 years. The number of male and female subjects was comparable, amounting to 493 (48.8%) and 517 (51.2%), respectively. Stenotic coronary arteries were detected in 699 patients (74.1%). The number of women without hemodynamically significant lesions was twice as large than that of men (210 [67.5%] vs. 101 [32.5%]). Among the examined patients with non-stenotic atherosclerosis of the coronary arteries, 241 patients (77.4%) were diagnosed with coronary microvascular dysfunction, 19 (6.1%) with vasospasm of the coronary arteries, and 2 patients (0.6%) were diagnosed with a combination of vasospastic and microvascular angina. In 36 (73.5%) of 49 patients, a segmental decrease in longitudinal strain of the apex/individual apical segments of the left ventricle was found. In patients without obvious micro- and macrovascular pathology, the interventricular septum was significant enlarged. In 9 (18.4%) of 49 patients, a diagnosis of hypertrophic cardiomyopathy was established.Conclusion. Patients with ischemia with no obstructive coronary arteries require careful examination and compari-son of clinical signs with the results of objective tests. Understanding the prevalence and mechanisms of the problem is a key to improving the diagnosis and treatment of cardiovascular complications in this group.